The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsomega.9b03314
|View full text |Cite
|
Sign up to set email alerts
|

Sodium, Potassium, and Lithium Complexes of Phenanthroline and Diclofenac: First Report on Anticancer Studies

Abstract: Diclofenac or 2-[(2′,6′-dichlorophenyl)amino]phenyl}acetic acid (dcf) is a nonsteroidal anti-inflammatory drug, and 1,10-phenanthroline (phen) is a well-known enzyme inhibitor. In this study, three new alkali metal complexes (1–3) containing both phen and dcf were prepared, and their structures were characterized by a variety of analytical techniques including infrared and UV–vis spectroscopy, 1H NMR and 13C NMR elemental analysis, mass spectrometry, and single-crystal X-ray diffraction analysis. In these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Several reports have been published on the synthesis of water‐soluble metal complexes of phenanthroline [ 22–24 ] which in all cases, the Phen ligand adopts a chelating fashion via N1 and N2 atoms and form a five‐membered ring. [ 25 ] On the other hand, Hamed et al [ 26 ] reported that FA could coordinate with some transition metals such as Fe(ΙΙΙ) and Cu(ΙΙ) via COOH, resulting in a significant increase in the solubility and absorption of FA complexes compared with free FA. In this regard, we performed a simple solubility test that the results showed that the [Zn(Phen)FA] complex could be dissolved in water at a ratio of 1.53 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have been published on the synthesis of water‐soluble metal complexes of phenanthroline [ 22–24 ] which in all cases, the Phen ligand adopts a chelating fashion via N1 and N2 atoms and form a five‐membered ring. [ 25 ] On the other hand, Hamed et al [ 26 ] reported that FA could coordinate with some transition metals such as Fe(ΙΙΙ) and Cu(ΙΙ) via COOH, resulting in a significant increase in the solubility and absorption of FA complexes compared with free FA. In this regard, we performed a simple solubility test that the results showed that the [Zn(Phen)FA] complex could be dissolved in water at a ratio of 1.53 mg/ml.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a hemi-heptahydrate (3.5H) form was reported very recently [37]. Multi-component crystals of DIC-Na with organic agents such as phenanthroline [38] and L-proline [39] have also been reported. In particular, the DIC solubility achieved by forming the DIC-Na L-proline salt cocrystal was significantly higher than that of DIC-Na [39].…”
Section: Introductionmentioning
confidence: 98%
“…[2,7,[15][16][17][18] These metal ions play a crucial role in numerous biological pathways such as cellular diversity, partition, apoptosis, homeostasis, adjusting electrolyte balances, pH, and nerve impulses. [19,20] Additionally, they have an advantage over transition or lanthanide metal ions because most of the sblock cations are non-toxic, relatively cheap, and soluble in aqueous media. [21,22] Furthermore, their high coordination numbers increase coordination arrangements and prompt unusual supramolecular topologies.…”
Section: Introductionmentioning
confidence: 99%